Why collaborate in music therapy? Exploring advances in relation to interprofessional publication practices. (1st June 2016) - Short, Alison; Heiderscheit, Annie
Abstract : Background : Based in humanities and influenced by individual research practices, the profession of music therapy has limited evidence of collaboration compared to medical, nursing and allied health fields. Reviewing collaborative practices in other fields provides a rationale for interprofessional collaborative practices in music therapy. Objective : The presentation aims to compare interprofessional collaborative practices across music therapy and allied health fields, leading to guidelines for collaboration in music therapy. Methods : Utilizing key informants from large international research institute, journals representing both European and American publications were selected from medicine, nursing and allied health. Leading music therapy journals from Europe and the America were selected. Journals were investigated for collaborative publications based on selection criteria, with a view toward understanding the impact and nature of the research. Results were compiled and compared. Discussion : Published advances in music therapy have typically occurred within the model of the sole researcher. The field of music therapy needs to urgently address interprofessional collaborative practices to advance in the future. Conclusions : Interprofessional collaborative practice is a priority for advancement of professional music therapy, and guidelines are proposed to support this development.